In-plant training at Healthcare Pharmaceuticals Limited - Rashid, Nowrin; Chowdhury, Tania Ahmed (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2021.